Militancy and identity politics in Assam - Srikanth, H. (2000)
With the state getting tougher and the public turning against them, the militants in Assam are clearly on the defensive today. Militancy in Assam is not a mere law and order problem but a reflection of a deeper malaise affecting the whole society. Neither can it be dubbed as radical politics of the marginalised communities against hegemonising forces. Politics of identity in Assam is basically trapped in the world of appearances, fighting imaginary enemies, and drawing strength from prejudices and misconceptions of groups about themselves and others. Without an understanding of the material and ideological roots that gives birth to militancy, restoring peace in Assam would be an uphill task. - Reproduced
Keywords: Assam - Politics and government; Politics and government